2011
DOI: 10.1007/s12010-011-9458-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Production Process of Optically Pure d-Lactic Acid from Raw Glycerol Using Engineered Escherichia coli Strains

Abstract: Glycerol has become an ideal feedstock for producing fuels and chemicals. Here, five technological schemes for optically pure D: -lactic acid production from raw glycerol were designed, simulated, and economically assessed based on five fermentative scenarios using engineered Escherichia coli strains. Fermentative scenarios considered different qualities of glycerol (pure, 98 wt.%, and crude, 85 wt.%) with concentrations ranging from 20 to 60 g/l in the fermentation media, and two fermentation stages were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 48 publications
0
7
0
4
Order By: Relevance
“…With a current production cost on the order of a dollar per kg (Posada et al 2012), even the highest producing strains generate a culture having lactic acid valued at less than $0.25 per liter. At such a low value for the fermentation product, the cost of the medium and operating conditions become critical in achieving an economic target for lactic acid production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a current production cost on the order of a dollar per kg (Posada et al 2012), even the highest producing strains generate a culture having lactic acid valued at less than $0.25 per liter. At such a low value for the fermentation product, the cost of the medium and operating conditions become critical in achieving an economic target for lactic acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Modifying the E. coli strain by replacing the native D-LDH with an L-LDH, blocking the methylglyoxal pathway, and preventing reassimilation of L-lactate by eliminating a native aerobic L-LDH led to 50 g L-lactate l -1 with 99.9 % optical purity from 56 g crude glycerol l -1 in 84 h (Mazumdar et al 2013). An economic assessment of the conversion of glycerol to D-lactic acid by engineered E. coli indicated that the use of crude glycerol represents less than 8 % of the production cost, and that the process could be a profitable use for glycerol (Posada et al 2012). Moreover, the success of the conversion depends mostly on the fermentation, and in particular the ability of strains to convert completely high concentrations of glycerol.…”
Section: Decrease Of By-products From Glycerolmentioning
confidence: 99%
“…Accordingly, it is necessary to find a new effective method to utilized this amount of crude glycerol. The research on production 1,3-PD from crude glycerol by microbiological way is extensively described worldwide e.g., (Hiremath et al 2011; Mendes et al 2011; Vaidyanathan et al 2011; Chatzifragkou et al 2011; Wilkens et al 2012; Ringel et al 2012), but only a few papers concern the production of lactic acid from this by-product, and moreover, publications concentrate mainly on genetic engineered strains (Posada et al 2012; Ruhal & Choudhury 2012); at the same time only a few papers discuss lactic acid production from other renewable resources (Hofvendahl & Hahn-Hägerdal 2000; Yadav et al 2011). During our work it occurred that Cl.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время, учитывая объемы производства биодизеля в мире -более 11 млн т в 2008 году с ежегодным последующим увеличением на 8−10 % [15], а также количество обра-зующегося в качестве отходов технического глицерина -10 % от получаемого биодизеля [13], становится понятно, что для эффективного использования такого отхода в качестве субстрата в биотехнологических процессах его содержание в среде культивирования продуцентов прак-тически ценных микробных метаболитов должно быть как можно выше.…”
unclassified
“…4). Возможность исключения из среды хлорида калия объяс-няется наличием достаточно высокого содержания К + в составе технического глицерина [11,15]. В данных исследованиях концентрация технического глицерина в среде составляла 2 %.…”
unclassified